2017
DOI: 10.1016/j.cis.2016.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Bulk and nanoscale polypeptide based polyelectrolyte complexes

Abstract: Polyelectrolyte complexes (PECs) formed using polypeptides have great potential for developing new self-assembled materials, in particular for the development of drug and gene delivery vehicles. This review discusses the latest advancements in PECs formed using polypeptides as the polyanion and/or the polycation in both polyelectrolyte complexes that form bulk materials and block copolymer complexes that form nanoscale assemblies such as PEC micelles and other self-assembled structures. We highlight the import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 128 publications
0
45
0
Order By: Relevance
“…These results suggest that a lack of charge screening in pure water prevents annealing of PIC chains into ordered complexes (vide infra), while conversely excess charge screening in higher salt concentrations leads to weakened complexation and is PIC length dependent. 5,6 Finally, elevated temperature (80 °C for 1.5 h) was found to have no visible effect on a 5.0 wt % (M O A) 155 E/K 60 hydrogel in 1× PBS, showing that DCH PIC possess good thermal stability.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…These results suggest that a lack of charge screening in pure water prevents annealing of PIC chains into ordered complexes (vide infra), while conversely excess charge screening in higher salt concentrations leads to weakened complexation and is PIC length dependent. 5,6 Finally, elevated temperature (80 °C for 1.5 h) was found to have no visible effect on a 5.0 wt % (M O A) 155 E/K 60 hydrogel in 1× PBS, showing that DCH PIC possess good thermal stability.…”
Section: Resultsmentioning
confidence: 91%
“…5,6 Blout and Idelson were the first to report that a mixture of homochiral poly(L-lysine-HCl), K, and poly(L-glutamate-Na), E, in water gave rise to phase separation of PICs rich in β -sheet content. 9 Later studies confirmed this result and showed that while the mixture of L-lysine and L-glutamate homopolymers formed β -sheets, other combinations with L-ornithine or L-aspartate homopolymers gave only disordered PICs.…”
Section: Introductionmentioning
confidence: 99%
“…While structured fluids, such as molecular liquid crystals, have long been used to organize colloids at defects and interfaces (20,21,(36)(37)(38)(39), here, we exploit colloid affinity to the liquid constituents to change the energetically favored locations within the liquid-crystal bulk. This interplay of adhesion, interfacial tension, and elasticity potentially has implications in regulation of spatial organization in subcellular liquid droplets beyond the spindle, in primitive and synthetic cells, and other macromolecular droplets such as coacervates (25,(40)(41)(42). In the future, this system can be extended to elucidate how colloid adhesion and shape, together with fluid structure, direct spatiotemporal organization in structured fluids, which may inform the design of novel structured, soft materials.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting self-assembled core-shell nanoparticles are variously referred to as polyelectrolyte complex micelles (PCMs), polyion complex micelles, block ionomer complexes, or coacervate-core micelles by analogy to surfactant micellization, even though all components of the system are hydrophilic 6,7 . PCMs' ability to encapsulate hydrophilic molecules such as proteins and nucleic acids, as well as the extensive tunability offered by the block copolymer carrier architecture makes them attractive candidates for delivering therapeutic molecules in vivo [8][9][10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%